An evaluation of Ireland's sustainable freight transport policy - Xu Zhang; Eoin Plant; Nikolaos Valantasis Kanellos (Logistics, 2022)
Background: The Irish government has put forth sustainable transport policy measures, yet the emphasis is mainly on the active travel and sustainable mobility for passenger transport. Contrariwise, freight transport has not received equal consideration in policy measures, regulatory frameworks, and support schemes towards the low-carbon transition. This study seeks to address this imbalance. Methods: The paper proposes an adaptation of the ASI framework for freight transport and assesses the applicability of a number of international sustainable transport measures based on their potential sustainability impact if adopted in Ireland. The research applied a Policy Delphi Method to a heterogeneous expert panel. Results: The findings indicate that the current sustainable freight transport policy measures in Ireland are limited, and the paper suggests 38 measures for supply chains, maritime transport, rail transport and urban freight transport. The analysis further suggests that decarbonisation measures in Ireland should first formulate on the decarbonisation stages "avoid" and "shift", and then move to the "improve" stage, thus leading to a greater impact on decarbonising the freight sector. Conclusions: An "ASI for freight transport" framework is proposed as a taxonomy to systematically compare freight decarbonisation policy measures locally and internationally. This updated framework can serve as a new lens to prioritise sustainable freight policy measures. Recommendations are proposed for developing policy measures for sustainable freight transport in Ireland.
Keywords: 650; avoid-shift-improve (ASI) approach; decarbonisation; Delphi method; Ireland; logistics; policy; policy Delphi; road freight; sustainability